Respuesta :

y + 7 = 3x.....y = 3x - 7
so we sub in 3x - 7 for y in the other equation

6x - 2y = 12
6x - 2(3x - 7) = 12
6x - 6x + 14 = 12
6x - 6x = 12 - 14
0 = -2 (incorrect)....no solution

Little tip :
if ur answer comes out with unequal amounts such as : 1 = 4, or 2 = 3, or 0 = -2...then there will be no solutions.
if ur answer comes out with equal amounts such as : 2 = 2, 3 = 3,0 = 0....then there will be infinite solutions.
if ur answer comes out with a variable equaling something...y = 4, x = 2, then there is 1 solution